2018
DOI: 10.1038/s41598-018-27772-9
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin maintenance dose Prediction for Patients undergoing heart valve replacement— a hybrid model with genetic algorithm and Back-Propagation neural network

Abstract: Warfarin is the most recommended anticoagulant drug for patients undergoing heart valve replacement. However, due to the narrow therapeutic window and individual dose, the use of warfarin needs more advanced technology. We used the data collected from a multi-central registered clinical system all over China about the patients who have undergone heart valve replacement, subsequently divided into three groups (training group: 10673 cases; internal validation group: 3558 cases; external validation group: 1463 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…To date, no study has been speci cally designed to address this concern. Our previous studies found an extremely low prediction accuracy in the low-dose group (0.0% by BPNN [11] and 9.1% by ANFIS [12]) and high-dose group (0.0% by BPGA [10]). Considering the distribution of patients across different doses in the training set, the proportion in the medium-dose group was higher than that in the low-and high-dose groups (low-dose: 10.41%, medium-dose: 81.81%, high-dose: 7.78%).…”
Section: Reasons For Improved Prediction Property In Low-and High-dose Groupsmentioning
confidence: 85%
See 2 more Smart Citations
“…To date, no study has been speci cally designed to address this concern. Our previous studies found an extremely low prediction accuracy in the low-dose group (0.0% by BPNN [11] and 9.1% by ANFIS [12]) and high-dose group (0.0% by BPGA [10]). Considering the distribution of patients across different doses in the training set, the proportion in the medium-dose group was higher than that in the low-and high-dose groups (low-dose: 10.41%, medium-dose: 81.81%, high-dose: 7.78%).…”
Section: Reasons For Improved Prediction Property In Low-and High-dose Groupsmentioning
confidence: 85%
“…Recently, several arti cial intelligence modeling technologies, including support vector machines and a general regression neural network, have been used for warfarin dosage predication [34,35]; however, these models showed a relatively low predictive ability of < 50% in the ideal predicted percentage. Our study team has made numerous attempts in the eld of warfarin model development and achieved a 63% predictive accuracy based on BPGA and ANFIS models [10,36,12]. In this study, we further included 15,108 patients who underwent HVR from 35 centers and used balanced training set preprocessing with the equal random strati ed sampling method.…”
Section: Summary Of Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a complex non‐linear relationship may exist between stable warfarin dose and genetic and clinical factors 19 . Therefore, a machine learning approach has been extensively implemented in developing predictive algorithms of personalized precision warfarin dosing 14,20–22 …”
Section: Introductionmentioning
confidence: 99%
“…In clinical pharmacology, GAs have been explored in the context of pharmacokinetic/pharmacodynamic (PK/PD) model selection, 2,3 the optimization of sampling times for PK studies, 4 and as alternative structural models to the multicompartment mammillary models in a machine learning approach to PK/PD 5 …”
mentioning
confidence: 99%